Modeling an islamic student financing securitization - Bakri, Mohammed Hariri; Ismail, Shafinar; Al-Shami, Samer Ali Hussein; Zainal, Nurazilah; Ridzuan, Abdul Rahim (Korea Distribution Science Association, 2020)
The study investigates developing an Islamic student financing securitization model based on sukuk structures. This study employs sample of descriptive, analytical, and comparative analyses utilized to discuss a novel framework of Islamic securitization through the different structures of sukuk wakalah derived from asset securitization. The result served to investigate the use of Islamic student financing securitization in a Shariah-compliant manner, which would be implementable in Malaysia. It emphasized the sukuk structures based on the wakeel principle, which indicated a situation where a wakeel or representative appointment was made to manage a project on the behalf of the sukuk holder. The findings of this study supported the economic benefits obtained in the form of lower overall financing costs through the use of securitization for student financing in higher education. This paper offers important implications specifically for the creation of sukuk structures and issuing a highly graded and marketable sukuk, which are compliant towards global Shariah principles. The paper fills the gap perceived within the existing literature of Islamic finance by showing Islamic securitization via sukuk as a viable source of funds potential utilizable in stabilizing the securities market. It can also pose as a solution for securing a sustainable funding.